Effect of adding mineral oil to the effectiveness of Permethrin Emulsion spray droplets on plutella xylostella larvae - Omar, Dzolkhifli (Universiti Putra Malaysia Press, 1993)
The effectiveness of permethrin emulsion spray droplets with (10% v/v) and without mineral oil was evaluated in the laboratory by bioassay using larvae ofPlutella xylostella. A microtip nozzle was used to produce spray droplets ranging from 52 - 274 ~m in volume median diameter. The 2nd instar larvae were placed on treated leaf discs, and knockdown and mortality were recorded after 1 hand 24 h respectively. In both treatments, as droplet size decreased the dose also decreased without losing the effectiveness ofpermethrin indicating that small droplets were more ejjicient than large droplets. VVhen sprayed using droplet size between 70 ~m to 100 ~m, there was no increase in the effectiveness ofpermethrin from emulsion spray droplets plus mineral oil compared to emulsion spray droplets alone. However, for droplet sizes greater than 125 ~m, the effectiveness was reduced.